2017
DOI: 10.1038/s41598-017-04779-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of contrast enhanced ultrasound in patients with blunt abdominal trauma presenting to the emergency department: a systematic review and meta-analysis

Abstract: We aimed to investigate the diagnostic accuracy of contrast-enhanced ultrasound (CEUS) in evaluating blunt abdominal trauma for patients presenting to the emergency department. Electronic search of Scopus and Pubmed was performed from inception to September 2016. Human studies investigating the diagnostic accuracy of CEUS in identifying abdominal solid organ injuries were included. Risk of bias was assessed using the QUADAS tool. A total of 10 studies were included in the study and 9 of them were included for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The application of CEUS seems particularly promising. A recent meta-analysis of nine studies comparing CEUS to contrast-enhanced CT in adult blunt trauma patients showed excellent sensitivity for CEUS of 0.981 (95 % CI: 0.868-0.950) and a false-positive rate of 0.018 (95 % CI: 0.010-0.032) for identifying parenchymal injuries [61]. The accuracy of CEUS in adult trauma patients is close to the sensitivity and specificity of contrast-enhanced CT. CEUS seems to be especially relevant for the up to 37 % of pediatric trauma patients that have abdominal parenchymal injuries verified on CT [62,63] but did not show evidence of free abdominal fluid on conventional B-mode ultrasound.…”
Section: Ganzkörper-computertomografie (Gkct)mentioning
confidence: 99%
“…The application of CEUS seems particularly promising. A recent meta-analysis of nine studies comparing CEUS to contrast-enhanced CT in adult blunt trauma patients showed excellent sensitivity for CEUS of 0.981 (95 % CI: 0.868-0.950) and a false-positive rate of 0.018 (95 % CI: 0.010-0.032) for identifying parenchymal injuries [61]. The accuracy of CEUS in adult trauma patients is close to the sensitivity and specificity of contrast-enhanced CT. CEUS seems to be especially relevant for the up to 37 % of pediatric trauma patients that have abdominal parenchymal injuries verified on CT [62,63] but did not show evidence of free abdominal fluid on conventional B-mode ultrasound.…”
Section: Ganzkörper-computertomografie (Gkct)mentioning
confidence: 99%
“…41 In a meta-analysis consisting of nine studies, the sensitivity and false-positive rate for detecting hepatic injury using CEUS was 94 and 1%. 42 CEUS can be considered as first-line imaging in centers where ultrasound is part of the initial trauma screening protocol. 43,44 More importantly, it is especially useful for serial monitoring for conservatively managed patients without exposing them to further radiation.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Contrast-enhanced ultrasonography (CEUS) which is a relatively novel modality with microbubble-based contrast agents have provided real-time anatomic and functional information in the study of microvascular fow in patients with SA-AKI without ionising radiation 16. Currently, CEUS has become widely used in the emergency department for evaluating cases of abdominal blunt trauma17; however, the use of CEUS in SA-AK cases is limited and it remains unclear whether it can provide useful information for predicting the development.…”
Section: Introductionmentioning
confidence: 99%